Satisfaction in close relationships - Sternberg, Robert J.; Hojjat, Mahzad (Guilford, 1997)
Prologue [by] George Levinger Part 1. Models of love and satisfaction in close relationships * Marital satisfaction in evolutionary psychological perspective / Todd K. Shackelford and David M. Buss * Attachment and relationship satisfaction across the lifespan / Lilah Raynor Koski and Phillip R. Shaver * Love and satisfaction / Susan S. Hendrick and Clyde Hendrick * A hierarchical model of love and its prediction of satisfaction in close relationships / Michael L. Barnes and Robert J. Sternberg * Philosophy of life as a model of relationship satisfaction / Mahzad Hojjat Part 2. Satisfaction over the course of close relationships * A temporal model of relationship satisfaction and stability / Ellen Berscheid and Jason Lopes * Marital satisfaction and spousal interaction / Judith A. Feeney, Patricia Noller and Carla Ward * Rethinking satisfaction in personal relationships from a dialectical perspective / Larry A. Erbert and Steve W. Duck Part 3. Conflict and satisfaction in close relationships * Angry at your partner?: Think again / Clifford I. Notarius, Samuel L. Lashley and Debra J. Sullivan * Conflict and satisfaction in couples / Andrew Christensen and Pamela T. Walczynski * Marital quality: A new theoretical perspective / Frank D. Fincham, Steven R. H. Beach and Susan I. Kemp-Fincham Part 4. Psychotherapy and satisfaction in close relationships * Acceptance in couple therapy and its implications for the treatment of depression / James V. Cordova and Neil S. Jacobson * The erosion of marital satisfaction over time and how to prevent it / Mari L. Clements, Allan D. Cordova, Howard J. Markman and Jean-Philippe Laurenceau * A schema-focused perspective on satisfaction in close relationships / Jeffrey Young and Vicki Gluhoski Part 5. Conclusion Satisfaction in close relationships: Challenges for the 21st century / Mark A. Whisman